Partial least squares modelling of attitudes of students towards learning statistics - Hassan Rahnaward Ghulami,; Mohd Rashid Ab Hamid,; Roslinazairimah Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Attitudes of students are vital in determining the perceived achievements in statistics subject. Therefore, this study investigates the relationship of attitudes of students towards learning statistics using several constructs which are affect, cognitive, value, difficulty, interest, effort and perceived achievement in statistics subject. Structural Equation Modelling – Partial Least Squares methodology was used to assess the hypothesised model that linked all the constructs of attitudes of students with the perceived achievement. The questionnaire was adopted from previous study and distributed to undergraduate students at Universiti Malaysia Pahang. From the analysis, it reveals that all the relationships in the hypothesised model were significant at p < 0.05 and this shows that all constructs of attitudes of students play a vital role in learning statistics. In short, this study reinforces the understanding of students’ attitude and could be a step forward for the lecturer to arouse the students’ interest in the teaching and learning process particularly for statistics.